Atmospheric recycling of agricultural evapotranspiration in the Tarim Basin - Shi, Kaifang; Li, Tiejian; Zhao, Jie; Su, Yang; Gao, Jian; Li, Jiaye (Frontiers in Earth Science, 2022)
Precipitation recycling, defined as that precipitation in a region is partially contributed by evapotranspiration from the same region, is the interaction between terrestrial hydrology and atmospheric processes, and plays a crucial role in forming water resources. For agricultural lands, the evapotranspiration of irrigation water alters local climate by reprecipitation in surrounding regions, which can also be analyzed from the viewpoint of precipitation recycling. As the largest endorheic basin in China, the Tarim Basin has strong precipitation recycling contributed by the surrounding mountains, as well as large irrigation areas producing high-quality cotton, which makes it an appropriate study case for the recycling of irrigation water. In this paper, we calculate the water vapor sources of precipitation (WSoP) and the reprecipitation of evapotranspiration (RPoET) in the Tarim Basin by using the Water Accounting Model - Two Layers, analyze their spatial distributions, and find the moisture recycling ratio of the basin as 15.4%. We set up comparative scenarios of evapotranspiration increase by irrigation areas in different locations of the Tarim Basin, and study their difference in reprecipitation and moisture recycling. Results show that the evapotranspiration increase in different locations has a marginal reprecipitation ratio ranging from 8% to 24%, and further boosts the whole basin’s moisture recycling ratio by 0.11% to 0.29%. Significant difference among the scenarios proves that the location of irrigation areas affects the reprecipitation of its evapotranspiration, and the optimized moisture recycling can benefit water resource and ecosystem conditions inside the basin. In summary, this work would be useful to provide a practical basis for irrigation planning by considering the land-atmosphere interaction.